DEVELOPMENT OF MULTIPARTICULATE FORMULATION AND EVALUATION OF COLON TARGETED DRUG DELIVERY SYSTEM OF CIPROFLOXACIN: IN VIVO STUDY WITH INDUCED COLITIS MODEL IN RATS - Rangari, Nalanda Tulsiram; Puranik, Prashant K (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this research work was to develop a multiparticulate containing chitosan and guar gum for the treatment of ulcerative colitis. Method: Method for the formulation of multiparticulate was done by extrusion-spheronization method using Eudragit L-100 and Eudragit S-100 as a coating solution and ciprofloxacin as a model drug. Result: Result from preliminary trial batches was previously assessed for physicochemical characterization, in vitro release, ex vivo mucoadhesion study, swelling studies, and in vivo evaluation and showed that the formulations appeared to be a good candidate to deliver the drug to the colon. Box-Behnken design was used to statistically optimize the formulation parameters and evaluate the main effects, interaction effects, and quadratic effects of the process parameters of enteric-coated multiparticulate on drug polymer ratio and coat composition. In this work, the effectiveness of optimized batch (C4) in the treatment of inflammatory bowel disease was evaluated. Experimentally, colitis was induced by rectal instillation of 2, 4, 6, trinitrobenzene sulfonic acid into male Wistar rats. The histological evaluations were done as inflammatory indices. In vivo gamma scintigraphy studies of multiparticulate without a drug demonstrate degradation of multiparticulate whenever they reach colon. Conclusion: The conclusion from results of studies such as gamma scintigraphy and histological study of optimized formulation (C4) clearly indicates that there is a great potential in delivery of ciprofloxacin to the colonic region. The animals treated with ciprofloxacin (C4) formulation had an improvement in pathology and may be useful for the treatment of inflammatory bowel disease. Keywords: Chitosan, Guar gum, Ciprofloxacin, Gamma scintigraphy, Histology, Ulcerative colitis, Box-Behnken design.